2016
DOI: 10.4103/0259-1162.183564
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of esmolol and dexmedetomidine on hemodynamic responses to carbon dioxide pneumoperitoneum during laparoscopic surgery

Abstract: Background:Carbon dioxide pneumoperitoneum for laparoscopic surgery increases arterial pressures, heart rate (HR), and systemic vascular resistance. In this randomized, single-blind, placebo-controlled clinical study, we investigated and compared the efficacy of esmolol and dexmedetomidine to provide perioperative hemodynamic stability in patients undergoing laparoscopic cholecystectomy.Methods:Sixty patients, of either sex undergoing elective laparoscopic cholecystectomy, were randomly allocated into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Similarly, Zhang et al [27] found IO esmolol can effectively reduce the cardiovascular responses in operation, sustain hemodynamic stable, reduce myocardial oxygen consumption, and prevent perioperative adverse cardiovascular events during laparoscopic surgery for gastrointestinal cancer. Also, Verma et al [5] and Bhattacharjee et al [28] in placebo-controlled study, found both esmolol and diltiazem[5] and dexmedetomidine[28] infusions, provided stable IO hemodynamics and protected against stress response triggered by pneumoperitoneum during laparoscopic surgery, but esmolol significantly lowered HR and BP than in diltiazem at the creation of pneumoperitoneum. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhang et al [27] found IO esmolol can effectively reduce the cardiovascular responses in operation, sustain hemodynamic stable, reduce myocardial oxygen consumption, and prevent perioperative adverse cardiovascular events during laparoscopic surgery for gastrointestinal cancer. Also, Verma et al [5] and Bhattacharjee et al [28] in placebo-controlled study, found both esmolol and diltiazem[5] and dexmedetomidine[28] infusions, provided stable IO hemodynamics and protected against stress response triggered by pneumoperitoneum during laparoscopic surgery, but esmolol significantly lowered HR and BP than in diltiazem at the creation of pneumoperitoneum. [29]…”
Section: Discussionmentioning
confidence: 99%
“…In support of this finding, Sharma et al [36] , in placebo-controlled study, reported that both dexmedetomidine and esmolol suppressed hemodynamic responses to intubation when compared to placebo. Also, Verma et al [19] and Bhattacharjee et al [37] in placebo-controlled study, found both esmolol and diltiazem [19] or dexmedetomidine [37] infusions, provided stable IO hemodynamics and protected against stress response triggered by pneumoperitoneum during laparoscopic surgery, but esmolol induced significantly lower HR and blood pressures than in diltiazem at the creation of pneumoperitoneum [19] . In another comparative study, Prajwal Patel et al [38] found both esmolol and labetalol attenuated hemodynamic response, but if patient has raised blood pressure, esmolol is a good option in blunting the response.…”
Section: Resultsmentioning
confidence: 97%
“…With the development of aging society, the number of elderly patients with CRC have increased gradually (18). According to literature, carbon dioxide pneumoperitoneum may threaten the life of patients undergoing laparoscopic surgery (19,20). In particular, the postoperative recovery of elderly patients is often affected by anesthesia and other factors (21), and it can also directly affect the cost of treatment, length of stay, and morbidity (22).…”
Section: Discussionmentioning
confidence: 99%